Toilet Phobia and Toilet Refusal In Children - Wagner, Catharina; Niemczyk, Justine; von Gontard, Alexander (Klinische Pädiatrie, 2017)
Objective: Toilet refusal syndrome (TRS) is a common disorder in toddlers, defined by use of diapers and refusal of toilet for defecation, while toilet phobia (TP) is a rare disorder in which toilets are avoided completely. Both disorders have not been described systematically in children, yet. Therefore, the aim was to present typical case vignettes illustrating different clinical presentations of TP and TRS.Methods: 5 typical cases were selected from all patients presented at a specialized outpatient clinic for incontinence at a tertiary university hospital during the last 3 years.Results: The first case is a girl with incontinence and no behavioral comorbidities, for whom treatment was more complicated than expected because of her TP. Second, a boy with an IQ on the border to mild intellectual disability will be presented, who revealed phobias regarding the toilet. Case 3 is exemplary for a group of patients with TRS, who also have ODD and show oppositional behavior in different situations. Cases 4 and 5 show “classical” TRS with constipation following painful defecation. Similarities and differences of TRS and TP, the current state of research, diagnostic and management recommendations are presented in detail.Conclusion: TRS in preschool children is a common condition, associated with high rates of constipation and behavioral problems. In contrast, TP is rarer and harder to recognize for pediatricians, but is often accompanied with somatic and behavioral problems, as well. Although there is a paucity of studies on these pediatric disorders, pediatricians should keep them in mind.